Disseminated tuberculosis presenting as massive lower gastrointestinal bleeding - Nehal Aggarwal; Subodh Kumar Mahto; Akanskha Singh; Kritika Gupta; Ankita Aneja; Anu Singh; Atul Goel (Journal of Family Medicine and Primary Care, 2020)
Intestinal tuberculosis has varied clinical presentations and often requires high index of suspicion for clinching the diagnosis. We report a case of an 18-year-old male who presented with abrupt onset of massive lower gastrointestinal bleeding and was diagnosed to have ileocecal tuberculosis. This case signifies the need to consider the possibility of intestinal tuberculosis as a cause of severe hematochezia among other etiologies to prevent mortality and morbidity.